О датировке Софии Киевской - Михеев, С.М. (Археологія, 2011)
В статье разбираются аргументы, позволяющие датировать строительство Софийского собора в Киеве. Близкие параллели
со Спасским собором в Чернигове, Софийским собором в Новгороде и наличие на стенах Софии Киевской
двух датированных граффити 6541 (1032—1034) и 6547 (1038—1039) годов позволяют утверждать, что храм был возведен
в промежутке между серединой 1020х
и концом 1030х
годов и не мог быть построен ни раньше, ни позже. In the article, arguments that allow establishing the date of the construction of the Saint Sophia Cathedral in Kyiv are
considered. Close parallels with the Saviour Cathedral in Chernihiv and with the Saint Sophia Cathedral in Novhorod, as well
as two dated graffiti in the Saint Sophia in Kyiv of 6541 (1032—1034) and of 6547 (1038—1039) allow the author to confirm
that the cathedral was erected within the period from the middle of the 1020s
and the end of the 1030s,
and that it could not
have been built neither earlier, nor later.